2020
DOI: 10.31234/osf.io/w84pu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parental Responsiveness During Musical and Non-Musical Engagement in Preschoolers with ASD

Abstract: Parent-child play interactions offer an important avenue for supporting social development in children with autism spectrum disorder (ASD). Musical play is a natural and ubiquitous form of parent-child play. As a familiar, reinforcing, and predictable activity, musical play may support parent-child interactions by scaffolding children’s attention to the play activities, while also providing parents with a familiar and accessible context to promote parental responsiveness. However, musical play may also impede … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The current research showed that the musical intervention not only created a positive place for the parent-infant dyads but also enhanced the parents' abilities to observe their infants' communicative behaviors, and to perceive and respond to their babys' cues. This finding is consistent with Boorom et al (2020), who examined the influence of parent-child musical engagements on parents' responsiveness. Although the authors focused on preschool children with autism and their parents, their findings shed light on the bi-directional impact of musical experiences.…”
Section: Discussionsupporting
confidence: 89%
“…The current research showed that the musical intervention not only created a positive place for the parent-infant dyads but also enhanced the parents' abilities to observe their infants' communicative behaviors, and to perceive and respond to their babys' cues. This finding is consistent with Boorom et al (2020), who examined the influence of parent-child musical engagements on parents' responsiveness. Although the authors focused on preschool children with autism and their parents, their findings shed light on the bi-directional impact of musical experiences.…”
Section: Discussionsupporting
confidence: 89%
“…Investigations of MSB must consider the bidirectionality of the interaction and the needs and goals of both social partners. For example, musical activities between parents and their child with a neurodevelopmental disability are increasingly recognized as modulating parent behaviors such as parent responsiveness (e.g., physically supporting child's play through contingent imitation) (Boorom, Muñoz, Xin, Watson, & Lense, 2020; Thompson, Shanahan, & Gordon, 2019) and parent mood (Williams, Berthelsen, Nicholson, Walker, & Abad, 2012), thus enhancing the likelihood of child engagement downstream. Music and song may be a particularly meaningful platform for social communication in light of the altered language and social communication abilities in ASD and Williams syndrome (Mervis & Velleman, 2011; Tager-Flusberg, 2000).…”
mentioning
confidence: 99%
“…Parents of young children with ASD reported that musical activities (e.g., family-centered music therapy) provided an interactive context in which they could share a play experience with their children (Thompson, 2018; Thompson et al, 2019). Parents of children with ASD also provided more physical play responses to their child during musical versus non-musical toy play (e.g., imitating child; Boorom et al, 2020). As parent responsiveness is linked to children’s social communication development (e.g., Gulsrud et al, 2016), musical activities may provide a context conducive to parents being available for and responsive to their child in order to support their child’s social engagement.…”
Section: Musical Activities and Shared Attentionmentioning
confidence: 99%